Expansion of CD25-Negative Forkhead Box P3-Positive T Cells during HIV and Mycobacterium tuberculosis Infection - Angerami, Matías T.; Suarez, Guadalupe V.; Vecchione, María B.; Laufer, Natalia; Ameri, Diego; Ben, Graciela; Perez, Hector; Sued, Omar; Salomón, Horacio; Quiroga, María F. (Frontiers in Immunology, 2017)
Tuberculosis (TB) and HIV alter the immune system, and coinfected (HIV-TB) individuals usually present deregulations of T-lymphocytic immune response. We previously observed an increased frequency of “unconventional” CD4+CD25-FoxP3+ Treg (uTreg) population during HIV-TB disease. Therefore, we aimed to explore the phenotype and function of uTreg and conventional CD4+CD25+FoxP3+ Treg subsets (cTreg) in this context. We evaluated the expression of CD39, Programmed cell death protein 1 (PD1), (Glucocorticoid-induced tumour necrosis factor receptor) GITR and the effector / memory distribution by flow cytometry in cTreg and uTreg. Also, IL-10, TGF-β, IFN-γ production and the suppressor capacity of uTregs were analyzed in cocultures with effector lymphocytes and compared with the effect of Tregs. We found diminished expression of CD39 and higher levels of PD1 on uTreg compared to cTreg in both HIV-TB and healthy donors (HD). In addition, uTreg and cTreg showed differences in maturation status in both HIV-TB and HD groups, due to the expansion of Effector Memory uTregs. Interestingly, both HIV-TB and HD showed a pronounced production of IFN-gamma in uTreg population, though no significant differences were observed for IL-10 and TGF-β production between uTreg and cTreg. Moreover, IFN-γ+ cells were restricted to the CD39- uTreg population. Finally, when the suppressor capacity was evaluated, both uTreg and cTreg inhibited polyclonal T cell-proliferation and IFN-γ production in a similar extent. These findings suggest that uTregs, which are expanded during HIV-TB coinfection, exert regulatory functions in a similar way to cTregs despite an altered surface expression of Treg characteristic markers and differences in cytokine production.